(untitled) (Journal of Nepal Geological Society, 2020)
The Himalayan freshwater lakes embody treasure of the country, crystal-clear nature of which offers water for drinking, irrigation and other domestic purposes, and provides shelter to numerous species, preserve aquatic biodiversity and habitat of the area. Freshwater lake is one of the major sources of livelihood amenities in Nepal and replenishes groundwater, positively influence the quality of downstream watercourses. In the present study, 20 water samples were collected from different points of Rajarani Lake, and analyzed for water temperature, pH, electrical conductivity (EC), total dissolved solids (TDS), oxygen-reduction potential (ORP), turbidity, dissolved oxygen (DO),total hardness (TH), major cations (Ca2+, Mg2+, K+, Na+ and NH4+) and major anions (HCO3-, Cl-, NO3-, and PO43-). The acquired data were interpreted using multivariate statistical technique with principal component analysis (PCA) and cluster analysis (CA) to evaluate controlling factors and characteristics of sampling locations in the lake.PCA results demonstrated major three factors contributing to water quality in lake with a 73.89% of cumulative variance. Similarly, CA results characterized sampling locations into four clusters indicating differentiation in the chemical concentrations. Results of the assessment through PCA, CA and comparison with other Himalayan lakes indicated that Rajarani Lake is not severely affected by pollution because it is still unexplored and thus pristine in nature. This study suggests that water quality of lake environments needs to be further investigated, focusing on depth-wise and temporal levels for its sustainability.